دراسة دور Chat GPTفي إنجاز المهام التعليمية لطلاب اللغة الإنجليزية - Elhaj, Eman A.; Almaloul, Heba; Alalwi, Nour (Al-Qurtas, 2025)
This research explores the perspectives of EFL undergraduate students regarding the challenges and barriers associated with the use of Chat GPT. To analyze students’ engagement with this platform, a combination of qualitative and quantitative research methods was utilized. Data collection involved conducting, six semi-structured interviews and administering a 55 item closed-ended questionnaire. The findings revealed a consensus between the two methods, revealing that although Chat GPT offers significant assistance in areas such as grammar correction and idea generation, there are ongoing concerns regarding its ethical implications and its influence on independent learning. It is recommended that the establishment of clear guidelines is essential for the effective integration of Chat GPT into students’ academic practices while addressing ethical considerations. These guidelines should promote responsible usage and emphasize the importance of incorporating AI tools into various EFL learning activities